Practical implications of innovative corporate restructuring - E.S. Titova (Овощи России)
The importance of scientific efforts and practical implementation of innovative researches and technologies into unstable market environment are underlined in the article. This special model could improve efficiency of innovative enterprise management having specific targets of development and practice determinations.